1986
DOI: 10.1111/j.1365-2222.1986.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and late allergic bronchial reactions: physiological characteristics

Abstract: Twenty-four patients with asthma of suspected allergic origin were subjected to a total of twenty-five bronchial provocations with the relevant allergen. Eighteen of them reacted with bronchial obstruction: eleven with an isolated early reaction, five with a dual reaction and two with only a late reaction. Extensive lung function tests were performed. The patterns of early and late reactions were qualitatively very similar regarding variables of pulmonary physiological function, but there were quantitative dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Of interest, FEF 50% gradually decreased 6 and 24 hours after the allergen challenge, suggesting that the small airways contribute importantly to the late-phase asthmatic response. This is in agreement with the findings of Machado et al, 76 who similarly showed an immediate increase in FEF 50% after an allergen provocation, followed by a decrease in FEF 50% 6 hours later. Ahmed et al 77 studied the early asthmatic response to ragweed provocation, distinguishing reactors and nonreactors based on a 35% decrease in specific airway conductance.…”
Section: Effects Of Allergen Exposure On Small-airways Dysfunctionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of interest, FEF 50% gradually decreased 6 and 24 hours after the allergen challenge, suggesting that the small airways contribute importantly to the late-phase asthmatic response. This is in agreement with the findings of Machado et al, 76 who similarly showed an immediate increase in FEF 50% after an allergen provocation, followed by a decrease in FEF 50% 6 hours later. Ahmed et al 77 studied the early asthmatic response to ragweed provocation, distinguishing reactors and nonreactors based on a 35% decrease in specific airway conductance.…”
Section: Effects Of Allergen Exposure On Small-airways Dysfunctionsupporting
confidence: 92%
“…74 The role of the small airways in the allergic response has been investigated by the change in the FEF 50% after breathing a mixture of helium-oxygen compared with room air. 75,76 Because of the lower gas density of helium, it can be assumed that a higher increase in FEF 50% will indicate obstruction in the more proximal airways, which are flow dependent. Metzger et al 75 studied the helium-oxygen flow-volume curves in 12 asthmatic patients with both an early-and late-phase allergic response based on a 20% and 10% decrease in FEV 1 , respectively.…”
Section: Effects Of Allergen Exposure On Small-airways Dysfunctionmentioning
confidence: 99%
“…It has been stated that isolated LARs are associated primarily with LMW agents, reflecting non-IgE-dependent mechanisms. However, isolated LARs have also been documented after SIC with HMW allergens [117,131,132], although such reactions seem to be rare. It is likely that the association between isolated LARs and LMW agents results from a methodological bias: during SIC the dose of HMW allergens is progressively increased until an immediate 20% fall in FEV1 is obtained, while exposure to LMW agents is usually increased on separate days.…”
Section: Research Purposesmentioning
confidence: 99%
“…This early-phase reaction (EPR), similar to allergen provocation in the skin [11], lung [12,13] or nose [14], is characterized by clinical symptoms and local infiltration by inflammatory cells (mainly neutrophils) [8,15]. Bonini et al described a second clinical reaction, termed the late-phase reaction (LPR) following CPT, appearing i hour later, peaking at 6-8 hours after challenge, and slowly subsiding (over 24 hours or more).…”
mentioning
confidence: 98%